The Dark Side of Regulatory Economics: Evidence from the Salt Import Policy in Post-Soeharto Indonesia - Hidayat, Rahmad; Raman, Asrul (HK-Publishing, 2020)
Economics regulation by the state is indeed very necessary to ensure that the pursuit of profit does not conflict with social welfare. That is the reason why regulatory economics becomes really important. However, the context in this paper contradicts with the ideal substance of regulatory economics in which the government proactively provides incentives to remain entrenched monopolistic business practices while taking a dominant role in importing salt commodity through the issuance of a public policy that is more permissive and accommodating to those interests. This paper aims to describe the political dynamics in the formulation and implementation of salt import policy in Post-Soeharto Indonesia which was mainly characterized by the practice of unfair business competition. As descriptive qualitative research, this study utilized in-depth interviews, observation, document tracking, and document analysis techniques in which a number of bureaucrats, entrepreneurs, and salt farmers were used as informants to mine the data. The results of this study show that government intervention through Permendag No. 125/2015 does not reveal a pure orientation of